Comparison of novel approaches for expedited pathogen identification and antimicrobial susceptibility testing against routine blood culture diagnostics. (6th May 2021) - Knabl, L.; Huber, S.; Lass‐Flörl, C.; Fuchs, S.
Abstract: Blood stream infections pose a major challenge for clinicians as the immediate application of an appropriate antibiotic treatment is the vital factor to safe the patients' lives. This preliminary study compares three different systems promising fast pathogen identification and susceptibility testing in comparison to conventional blood culture (BC): (i) the rapid antimicrobial susceptibility testing protocol according to EUCAST in combination with the Sepsityper ® kit (sRAST), (ii) the direct inoculation method on the VITEK ® 2 system (dVIT) and (iii) testing with the Accelerate Pheno ® system (AccPh). All methods were assessed in terms of accuracy, time to result and usability. Twenty‐three BC samples obtained from patients suffering from proven sepsis were analysed in detail. Pathogen identification was successful in 95·6, 91·3 and 91·3% in sRAST, dVIT and AccPh, respectively. Categorical agreement in antimicrobial susceptibility testing was 89·5, 96 and 96·6%, respectively. Time to result from sample entry to reporting ranged from an average of 4·6 h for sRAST and 6·9 h for AccPh to 10·6 h for dVIT. These results imply a significant shortening of reporting times at considerably high agreement rates for these new diagnostic approaches. Abstract : Significance and Impact of the Study: Timely reporting of pathogen identification and antimicrobial susceptibility is crucial for patients suffering from sepsis. New approaches promising short turnaround times compared to conventional workup of blood cultures are seeking their way to routine laboratory implementation. This pilot study evaluates novel techniques for pathogen identification and antimicrobial susceptibility testing directly from positive blood cultures. The data indicate a considerable expediting in microbiological sepsis diagnosis without compromising result quality.